Interobserver agreement of contrast-enhanced harmonic endoscopic ultrasonography in the evaluation of solid pancreatic lesions - Soares, João-Bruno; Iglesias-Garcia, Julio; Gonçalves, Bruno; Lindkvist, Björn; Lariño-Noia, Jose; Bastos, Pedro; Caetano, Ana Célia; Ferreira, Aníbal; Pimentel-Nunes, Pedro; Lopes, Luís; Moutinho, Pedro; Dominguez-Muñoz, J. Enrique (Endoscopy International Open, 2015)
Background and study aims: Previous reports assessing the reproducibility of contrast-enhanced harmonic endoscopic ultrasonography (CH-EUS) in the evaluation of solid pancreatic lesions (SPLs) involved mainly experienced endosonographers. We aimed to assess the interobserver agreement (IOA) of CH-EUS in the evaluation of SPLs by endoscopists with different levels of experience in EUS and CH-EUS.Participants and methods: A cross-sectional observational multicenter study was designed and included 11 endoscopists who were divided into four groups according to their experience in EUS and CH-EUS: group A (long experience in EUS and CH-EUS); group B (short experience in EUS and CH-EUS); group C (long experience in EUS and no experience in CH-EUS); and group D (no experience in EUS or CH-EUS). The observers independently classified the patterns of 60 CH-EUS video sequences of 60 SPLs after a 20-minute training session. For each group, we calculated the IOA (kappa statistic, κ) of CH-EUS and the accuracy of CH-EUS for the diagnosis of pancreatic adenocarcinoma by comparing the pattern of CH-EUS indicative of pancreatic adenocarcinoma (hypo-enhanced contrast pattern) with the final diagnosis.Results: The overall IOA for CH-EUS was fair (κ = 0.32; 95 %CI 0.22 – 0.41). Group A (κ = 0.63; 95 %CI 0.45 – 0.85) had the highest IOA, followed by group C (κ = 0.54; 95 %CI 0.39 – 0.71), group B (κ = 0.38; 95 %CI 0.22 – 0.55), and group D (κ = 0.21; 95 %CI 0.07 – 0.36). The IOA of groups A and C was significantly higher than that of group D. No significant difference was seen between groups A, B, and C or between groups B and D in terms of IOA. Group A (area under the curve under summary receiver operating characteristic [AUROC] = 0.67; 95 %CI 0.58 – 0.75) had the highest accuracy for the diagnosis of pancreatic adenocarcinoma, followed by group C (AUROC = 0.58; 95 %CI 0.50 – 0.65), group B (AUROC = 0.55; 95 %CI 0.48 – 0.63), and group D (AUROC = 0.51; 95 %CI 0.43 – 0.58). The diagnostic accuracy of group A was not significantly different from that of group C, but it was significantly higher than that of groups B and D. No significant difference was seen between groups B, C, and D in terms of diagnostic accuracy.Conclusions: CH-EUS is reproducible in the evaluation of SPLs, even between endoscopists with no or limited experience in EUS and/or CH-EUS. Long experience in EUS is a major contributor to the IOA and diagnostic accuracy of CH-EUS.